Using participatory GIS and collaborative management approaches to enhance local actors’ participation in rangeland management: the case of Vulindlela, South Africa - Cho, M. A.; Onisimo, M.; Mabhaudhi, Tafadzwanashe (Informa UK Limited, 2023)
Participatory Geographic Information Systems (PGIS) is an empowering tool for the enhancement of local communities’ participation in the planning and management of natural resources. The inadequate involvement of local stakeholders in rangeland planning and management has been of great concern. Discussions on the role of PGIS and collaborative management approaches in promoting local involvement in rangeland management has not been clearly understood due to the scarcity of literature. This paper assessed how local participation in rangeland management can be enhanced using a combined collaborative management framework and PGIS approach. The objective was achieved through a focus group discussion, local ecological knowledge mapping and key informant interviews. The combined PGIS and collaborative management approach enabled the empowerment of local actors through knowledge enhancement, encouraged the practice of rangeland governance and the transfer of responsibility to local actors. This study provides a conceptual contribution toward the improvement of local actors’ participation in rangeland management.